1997
DOI: 10.1074/jbc.272.1.196
|View full text |Cite
|
Sign up to set email alerts
|

CspA, the Major Cold-shock Protein of Escherichia coli, Is an RNA Chaperone

Abstract: CspA, the major cold-shock protein of Escherichia coli, is dramatically induced during the cold-shock response. The amino acid sequence of CspA shows 43% identity to the "cold-shock domain" of the eukaryotic Y-box protein family, which interacts with RNA and DNA to regulate their functions. Here, we demonstrate that CspA binds to RNA as a chaperone. First, CspA cooperatively binds to heat-denatured single-stranded RNA if it is larger than 74 bases, causing a supershift in gel electrophoresis. A minimal concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
601
2
12

Year Published

1997
1997
2003
2003

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 598 publications
(632 citation statements)
references
References 27 publications
17
601
2
12
Order By: Relevance
“…in the repression of induction of CspA, CspB and CspG after acclimatization to cold shock . CspA has recently been shown to bind to RNA in vitro (Jiang et al, 1997). In this report, CspB, CspC and CspD from B. subtilis are shown to bind to RNA with moderately lower affinity than to the corresponding ssDNA.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…in the repression of induction of CspA, CspB and CspG after acclimatization to cold shock . CspA has recently been shown to bind to RNA in vitro (Jiang et al, 1997). In this report, CspB, CspC and CspD from B. subtilis are shown to bind to RNA with moderately lower affinity than to the corresponding ssDNA.…”
Section: Discussionmentioning
confidence: 69%
“…According to this finding, a minimal concentration of CspB for binding to 54mer RNA is 5 × 10 ¹6 M, which suggests that in vivo mRNA could be bound even more efficiently than the oligonucleotides used in our assays. By analogy, a minimal concentration of CspA from E. coli was shown to be necessary for co-operative binding to RNA in vitro (Jiang et al, 1997). 5Ј UTRs of cspB and cspC revealed a highly conserved motif (CS-box 1) at their 5Ј end, which could be a target for regulation of translation.…”
Section: Loss Of Csps Leads To An Increase In Levels Of Remaining Cspmentioning
confidence: 99%
“…Cold shock-induced proteins (Csps) have been well studied in Escherichia coli (Goldstein et al, 1990;Jones and Inouye, 1994;Jones et al, 1996). In contrast to hsps which are protein chaperones to help to refold the non-native proteins, prevent their aggregation or direct protein degradation (review in Becker and Craig, 1994), Csps have been shown to be RNA chaperones to prevent the formation of secondary structures in RNA at low temperature (Jones et al, 1996;Jiang et al, 1997). To our knowledge, cold shock proteins have not yet been found in human cells, thus, the e ects of cold shock on mammalian cells are poorly documented.…”
mentioning
confidence: 99%
“…CspA, the most prominent of the nine-member E. coli CSP family, accumulates up to 10% of total proteins during cold stress (Jiang et al, 1997). The three-dimensional structure of E. coli CspA forms a five-stranded ␤-barrel structure (Newkirk et al, 1994;Schindelin et al, 1994) that contains two consensus RNA-binding motifs (RNP1 and RNP2), which facilitate nucleic acid recognition/binding (Schroder et al, 1995).…”
mentioning
confidence: 99%
“…The three-dimensional structure of E. coli CspA forms a five-stranded ␤-barrel structure (Newkirk et al, 1994;Schindelin et al, 1994) that contains two consensus RNA-binding motifs (RNP1 and RNP2), which facilitate nucleic acid recognition/binding (Schroder et al, 1995). CspA has been hypothesized to prevent RNA secondary structure formation (Jiang et al, 1997), thereby enhancing translation at low temperature.…”
mentioning
confidence: 99%